From the Classroom to Social Action: The Impact of Project Based Learning on Students’ Anti-Corruption Awareness in Higher Education - Dyah Estyani Cahya; Olin Monalvia; Defika Putri Nastiti (Jurnal Kewarganegaraan, 2026)
Corruption in Indonesia has deepened beyond individual misconduct into structural and cultural dimensions, underscoring the urgent need for preventive approaches through education. However, the implementation of anti-corruption education in universities remains dominated by theoretical approach that minimizes practical action. This study aims to examine how the implementation of Project Based Learning in Anti-Corruption Education course transforms students’ understanding and attitudes, and generates a concrete impact on the target community. Using a descriptive qualitative approach with an impact orientation, this study involved 102 students in the Civic Education Program at Jambi University who simultaneously implemented two dimensions of social action: an anti-corruption educational campaigns on campus and in schools, and social experiments in the form of honesty cafeterias and stationary lending corners. Data were collected through student reflective videos, project documentation, and in-depth semi-structured interviews with nine teachers selected through purposive sampling, then analyzed thematically. The findings reveal a shift in student understanding from a cognitive-normative to a contextual-personal perspective, a transformation in attitude from knowledge recipients to active agents of change, and a positive response from the target community. This study indicates that the simultaneous combination of educational and experimental interventions within Project Based Learning framework produces a more comprehensive impact than a single intervention, although the transferability of the findings is limited to the specific context of Jambi University.